Working in multicultural environments: a conceptual analysis of the effects of spirituality, religiosity, and personal values on employee performance - Hashim, Junaidah (2011)
With growing globalization of business operations, along with the movements of goods and services across nations, increasing trends of movements of people from various national, cultural and religious backgrounds are being observed to organizations in almost all business sectors. This trend of the movements is changing the demographic compositions of workforce making the organizations more multicultural, multi-religious and diverse in nature. This paper presents a conceptual analysis of the effects of religiosity, spirituality, individual values on employee performance in multicultural organizations. The paper also highlights the moderating and mediating effects of individual values and organizational commitments. Based on exhaustive literature reviews, the paper developed some propositions that could be tested through empirical research in future. A conceptual framework is presented to guide future research, and implications for professional practice have been discussed at the end.